Global, regional, and national analyses of the burden among adult women of breast cancer attributable to diet high in red meat from 1990 to 2021: longitudinal observational study - Ding, Xiaoyun; Tang, Zhenning; Ma, Hang; Jiang, Can (Frontiers in Public Health, 2025)
BackgroundThe association between red meat consumption and breast cancer risk has been well established; however, it is crucial to understand the temporal trends, geographical variations, and socio-demographic factors that influence this risk among women aged 25–45. Consequently, this study seeks to investigate the impact of red meat consumption on breast cancer risk among adult women for the first time.MethodsData were extracted from the Global Burden of Disease (GBD) 2021 study to calculate age-standardized rates (ASR) for mortality and disability-adjusted life years (DALYs). Trends were assessed using estimated annual percentage change (EAPC) with linear regression analysis. Hierarchical clustering identified temporal trends, and examined the relationships between EAPC, ASR, DALYs, and the socio-demographic index (SDI).ResultsOur findings indicate that breast cancer-related deaths and DALYs attributable to high red meat consumption increased globally, rising from 44,492 deaths and 1,379,721 DALYs in 1990 to 79,956 deaths and 2,407,092 DALYs in 2021. In high SDI regions, age-standardized mortality (−1.47%) and DALYs (−1.48%) rates declined, while low-middle and high-middle SDI regions showed significant increases. Low SDI regions, despite lower absolute numbers, experienced sharp relative increases in both deaths and DALYs. Additionally, a nonlinear relationship between ASR and SDI was observed, with the burden peaking in moderate SDI regions.ConclusionThis study concludes the rising global burden of breast cancer in adult women associated with high red meat consumption, with particularly pronounced impacts in low and middle SDI regions.